2015
DOI: 10.1371/journal.pone.0143733
|View full text |Cite
|
Sign up to set email alerts
|

Predator Presence and Vegetation Density Affect Capture Rates and Detectability of Litoria aurea Tadpoles: Wide-Ranging Implications for a Common Survey Technique

Abstract: Trapping is a common sampling technique used to estimate fundamental population metrics of animal species such as abundance, survival and distribution. However, capture success for any trapping method can be heavily influenced by individuals’ behavioural plasticity, which in turn affects the accuracy of any population estimates derived from the data. Funnel trapping is one of the most common methods for sampling aquatic vertebrates, although, apart from fish studies, almost nothing is known about the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…We found that draining achieves this goal by increasing tadpole abundance in fish‐free ponds to over 140 times that of undrained ponds. However, a small amount of this increase may be attributed to tadpole detectability, which is increased by 4.3 times if gambusia are absent compared to present, using the method of minnow trapping (Sanders et al ). Even in cases where gambusia recolonized drained ponds prior to the beginning of the breeding season, on average the abundance of tadpoles in these ponds was still increased 7‐fold.…”
Section: Discussionmentioning
confidence: 99%
“…We found that draining achieves this goal by increasing tadpole abundance in fish‐free ponds to over 140 times that of undrained ponds. However, a small amount of this increase may be attributed to tadpole detectability, which is increased by 4.3 times if gambusia are absent compared to present, using the method of minnow trapping (Sanders et al ). Even in cases where gambusia recolonized drained ponds prior to the beginning of the breeding season, on average the abundance of tadpoles in these ponds was still increased 7‐fold.…”
Section: Discussionmentioning
confidence: 99%
“…Sanders et al (2015) compared the trapability of L. aurea tadpoles in mesocosms with and without G. holbrooki and found that tadpoles were over four times more likely to be captured when G. holbrooki was absent. Sanders et al (2015) compared the trapability of L. aurea tadpoles in mesocosms with and without G. holbrooki and found that tadpoles were over four times more likely to be captured when G. holbrooki was absent.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, L. aurea's breeding season overlaps with peak levels of G. holbrooki abundance (Pen & Potter 1991;Pyke 2005), reinforcing the importance for a proportion of ponds to remain fishfree. Sanders et al (2015) showed that L. aurea tadpole behaviour is altered in the presence of G. holbrooki, and many prey species exhibit a generalist response to functionally similar predators (Ferrari et al 2009). Previous studies that consider the conservation of L. aurea suggest that construction of habitat mosaics provides a suitable strategy to deal with breeding habitat preference and the avoidance of G. holbrooki (Hamer & Mahony 2007;Mahony et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations